2021
DOI: 10.1021/acs.cgd.1c00841
|View full text |Cite
|
Sign up to set email alerts
|

Crafting a Next-Generation Device Using Iron Oxide Thin Film: A Review

Abstract: Despite extensive research into novel materials, iron oxides remain fascinating and attract considerable attention because of their versatility, stability, ease of fabrication, low cost, natural abundance, and environmental friendliness. Because of their wealth of magnetic, optical, and electrical properties, iron oxides are particularly multifunctional materials that can be integrated into various devices. In this article, we will discuss the applications of iron oxide thin films in electronics (spintronics d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 274 publications
(587 reference statements)
0
14
0
Order By: Relevance
“…Recently, uncommon Fe 4 O 5 and Fe 5 O 6 phases were also discovered using special synthesis treatment . FeO and Fe 3 O 4 are only found in one crystal structure, while Fe 2 O 3 is discovered in various forms and different crystal structures, namely, γ-Fe 2 O 3 (maghemite), α-Fe 2 O 3 (hematite), ε-Fe 2 O 3 (luogufengite), β-Fe 2 O 3 , ζ-Fe 2 O 3 , η-Fe 2 O 3 , θ-Fe 2 O 3 , and ι-Fe 2 O 3 . Among them, FeO, Fe 3 O 4 , γ-Fe 2 O 3 , and α-Fe 2 O 3 are recognized as stable phase, while the rest are metastable . Here, we discuss briefly the types of iron oxides above in the subsections below.…”
Section: All Types Of Iron Oxides Phasesmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, uncommon Fe 4 O 5 and Fe 5 O 6 phases were also discovered using special synthesis treatment . FeO and Fe 3 O 4 are only found in one crystal structure, while Fe 2 O 3 is discovered in various forms and different crystal structures, namely, γ-Fe 2 O 3 (maghemite), α-Fe 2 O 3 (hematite), ε-Fe 2 O 3 (luogufengite), β-Fe 2 O 3 , ζ-Fe 2 O 3 , η-Fe 2 O 3 , θ-Fe 2 O 3 , and ι-Fe 2 O 3 . Among them, FeO, Fe 3 O 4 , γ-Fe 2 O 3 , and α-Fe 2 O 3 are recognized as stable phase, while the rest are metastable . Here, we discuss briefly the types of iron oxides above in the subsections below.…”
Section: All Types Of Iron Oxides Phasesmentioning
confidence: 99%
“…Green synthesis is also possible to decrease the toxicity of the energy conversion and storage device, which is important to the environmental impact . Iron oxides are considered to be one of the materials that could be implemented in energy conversion and storage applications, because of their excellent magnetic, electric, and optical properties. ,, Several studies have reported the green technology of iron oxides in energy conversion and storage applications. For instance, facile synthesis of gelatin-tethered iron oxide nanocomposites as high-performance anode materials for Li-ion batteries, Fe 3 O 4 /carbon nanocomposite prepared by flocculation of alginate via a Fe 3+ solution for application in Li-ion battery anode, green synthesis of Fe 3 O 4 nanoparticles using aqueous extracts of Pandanus odoratissimus leaves for an efficient bifunctional electrocatalytic activity for water splitting, which is applicable in hydrogen energy, and a facile and green synthesis through the solvent-free chemical condition of core–shell Fe 3 O 4 @PANI nanocomposite to enhance the triplet state population thus increasing the efficiency of the solar cells …”
Section: Recent Applications Of Nanometer-sized Iron Oxides Synthesiz...mentioning
confidence: 99%
See 3 more Smart Citations